2-(1H-Tetrazol-1-yl)thiazole: Complexation and copper-assisted tetrazole ring transformation. (1st October 2019) - Voitekhovich, Sergei V.; Grigoriev, Yuri V.; Lyakhov, Alexander S.; Matulis, Vadim E.; Ivashkevich, Ludmila S.; Ivashkevich, Oleg A.
Graphical abstract: Despite the arrangement of donor centers suggesting chelation, 2-(1 H -tetrazol-1-yl)thiazole is coordinated by only N 4 atom of the tetrazole cycle in copper(II) and cobalt(II) complexes. Under interaction with copper(II) chloride and ethanol it also undergoes tetrazole ring transformation leading to ethyl thiazol-2-ylcarbamimidate complex. Abstract: 2-(1 H -Tetrazol-1-yl)thiazole (tth), prepared by heterocyclization of 2-aminothiazole with triethyl orthoformate and sodium azide, was found to react with copper(II) chloride in ethanol giving a mixture of [Cu(tth)2 Cl2 ] n (1 ) and [Cu2 (ethc)2 Cl4 ]·2H2 O (2 ), where ethc is ethyl thiazol-2-ylcarbamimidate. Formation of complex2 with ethc ligand can be explained by tetrazole ring-opening reaction of tth followed by addition of ethanol to the intermediate N-(thiazol-2-yl)cyanamide (N-tca). This assumption was confirmed by isolation of complex2 under interaction of N-tca with copper(II) chloride in ethanol. Transformation of the tetrazole ring was not observed under interaction of tth and copper(II) chloride in 1, 2-dichloroethane/ethanol mixture, when1 and [Cu2 (tth)4 Cl4 ] (3 ) were isolated. Ligand tth was found to react with copper(II) tetrafluoroborate and cobalt(II) chloride giving [Cu(tth)2 (H2 O)4 ](BF4 )2 (4 ) and [Co(tth)2 Cl2 (H2 O)2 ]·2tth (5 ), correspondingly. Molecular crystals of tth and complexes1 –5 were characterized by X-ray single crystal analysis. In the complexes, tth acts as a monodentate ligand coordinated via the tetrazole ring N 4 atom.